A Case of Probable Amisulpride Induced Mania after Eight Months of Therapy. (9th October 2017) - Thapa, Prakash; Sharma, Rajasee
Abstract : Development of manic symptoms during treatment with atypical antipsychotics can be a troublesome side effect that has been described with most atypical antipsychotics. However, reports of amisulpride induced mania have been rare. Here, we report the case of an 18-year-old male patient diagnosed with schizophrenia, who developed manic symptoms while on treatment with amisulpride. While previous reports have described occurrence of mania within days to three months of treatment with amisulpride, we report a case where manic symptoms occurred after around eight months of therapy. We have also attempted to describe the possible risk factors based on the available case studies.